Hypopigmented Mycosis Fungoides in Type V Skin: A Report of 5 Cases - Ranthilaka R. Ranawaka; Priyanka H. Abeygunasekara; M. V. Chandu de Silva (Case Reports in Dermatological Medicine)
Five patients with type V skin were studied to describe the clinical manifestations, pathological features, and treatment response in hypopigmented mycosis fungoides (HMF). The mean age of patients was 22.4 years at diagnosis, with a mean of 36 months of diagnostic delay. Two were children aged 11 and 13 years. Skin patches were limited to sunlight-covered body areas. In tropical climate, exposure to natural sunlight possibly cured the lesions on sun-exposed areas at early stage of onset. HMF may frequently be misinterpreted as eczema, vitiligo, or progressive macular hypomelanosis clinically and histopathologically as seen in our case series.